2017
DOI: 10.1111/efp.12376
|View full text |Cite
|
Sign up to set email alerts
|

Ralstonia solanacearum decreases volumetric growth of trees and yield of kraft cellulose of Eucalyptus spp.

Abstract: Summary Ralstonia solanacearum is currently one of the most important plant pathogenic bacteria worldwide, with a wide geographical distribution and host diversity. The pathogen infects more than 200 plant species belonging to approximately 50 plant families, including Eucalyptus spp. Although, high losses have been reported in nurseries, little is known on the negative impact of the disease in the field. In this study, we evaluated the incidence of R. solanacearum and its effect on volumetric growth and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
8
1
2
Order By: Relevance
“…If the stems or branches of the plant are attacked, and are then cut and left for a while, they will release a milky white liquid, which is a bacterial colony. According to Ferreira et al (2017) and Coutinho and Wingfield (2017), eucalyptus plants infected with BWD show symptoms of wilting; yellowing of the leaves, which fall and leave bare plant stems without leaves; and when the stems are cut, the color of the xylem is changed and bacterial fluid is secreted. If the symptoms are severe, the tree will easily collapse due to infection and a defective root system.…”
Section: Discussionmentioning
confidence: 99%
“…If the stems or branches of the plant are attacked, and are then cut and left for a while, they will release a milky white liquid, which is a bacterial colony. According to Ferreira et al (2017) and Coutinho and Wingfield (2017), eucalyptus plants infected with BWD show symptoms of wilting; yellowing of the leaves, which fall and leave bare plant stems without leaves; and when the stems are cut, the color of the xylem is changed and bacterial fluid is secreted. If the symptoms are severe, the tree will easily collapse due to infection and a defective root system.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is a common exacerbator of disease symptoms, especially if trees have been poorly planted and have root knotting or other injuries (Alfenas et al, 2006;Coutinho & Wingfield, 2017). The disease can cause up to approximately 80% growth reductions, leading to reduced pulp production and considerable economic losses (Ferreira et al, 2017). It has recently been reported that R. solanacearum causes bacterial wilt in ironwood trees in Guam (Ayin et al, 2019).…”
Section: Ralstonia Solanacearum Species Complexmentioning
confidence: 99%
“…eucalypticola in South Africa (van Wyk et al, 2012) cause rapid wilting and eventual tree mortality (Roux & Wingfield, 2009). Among bacterial pathogens, Ralstonia pseudosolanacearum (Freitas et al, 2020) and R. solanacearum (Ferreira et al, 2018) have been considered as serious wilt pathogens of Eucalyptus in Brazil.…”
Section: Introductionmentioning
confidence: 99%